Introduction to credit risk modeling - Bluhm, Christian; Overbeck, Ludger; Wagner, Christoph (Chapman & Hall/CRC financial mathematics series, 2010)
"Preface Second Edition The first edition of this book appeared eight years ago. Since then the banking industry experienced a lot of change and challenges. The most recent financial crisis which started around May 2007 and lasted in its core period until early 2009 gave rise for a lot of scepticism whether credit risk models are appropriate to capture the true nature of risks inherent in credit portfolios in general and structured credit products in particular. In a recent article two of us discuss common credit risk modeling approaches in the light of the most recent crisis and invite readers to participate in the discussion; see [25]. A key observation in a discussion like the one in [25] is that the universe of available models and tools is sufficiently rich for doing a good job even in a severe crisis scenario as banks recently experienced it. What seems to be more critical is an appropriate model choice, parameterization of models, dealing with uncertainties, e.g., based on insufficient data, and communication of model outcomes to decision makers and executive senior management. These are the four main areas of challenge where we think that a lot of work and rethinking needs to be done in a p?ost-crisis ?reflection of credit risk models. In the first edition of this book we focussed on the description of common mathematical approaches to model credit portfolios. We did not change this philosophy for the second edition. Therefore, we left large parts of the book unchanged in its core message but supplemented the exposition with new model developments and with details we omitted in the first edition"